Subsidies in the renewable energy industry under the World Trade Organization regime and suggestion for Vietnam - TRAN, Ngoc Phuong (KDI School, 2022)
With a continuous increase in greenhouse gas emissions and an increase in global average temperature, climate change’s effects are predicted to grow more widespread and severe than ever before. Under this pressure, governments throughout the world have implemented various subsidy programs in an attempt to promote the expansion of the renewable energy sector. Similarly, in Vietnam, there is a growth in demand for subsidy programs to attract investments in this sector. However, the Vietnamese Government is obligated to maintain consistency of these programs regarding the WTO’s regulations. Realizing the situation, this study proposes suggestions for the Vietnamese Government to execute subsidy programs in the WTO context without being challenged by other WTO Members. WTO’s subsidy-related agreements, disputes settled under WTO, and incentives for developing the renewable energy industry in Vietnam will be analyzed for the scope of research. In conclusion, the use of incentives without conditions that subsidy recipients must use or purchase a certain proportion of equipment originating from local sources, the continuous application of the feed-in tariff program as well as the careful research of the import market are suggestions to execute support for renewable energy in Vietnam effectively.
Thesis(Master) -- KDI School: Master of Public Policy, 2022
Keywords: Energy industries--Vietnam; Foreign trade regulation